Genetic diversity and morphological characterization of different Adenium genotypes - Deepak, S; Padmapriya, S; Sathiyamurthy, V A; Renuka, R; Santhanakrishnan, V P (Plant Science Today, 2024)
The current study at Tamil Nadu Agricultural University in 2023–2024 aims to characterize the morphological features and genetic diversity of 20 Adenium genotypes. The research was performed with various vegetative and floral traits, revealing significant variations among genotypes. Notable differences were observed in plant height, branching habit, caudex circumference, leaf characteristics and floral features. Genetic analysis showed high genotypic and phenotypic coefficients of variation for traits like petal thickness, number of branches per plant and diameter of the corolla tube. These traits also exhibited high heritability and genetic advance, indicating potential for improvement through selective breeding. Other traits, such as plant height and leaf dimensions, showed moderate heritability and lower genetic advance, suggesting the influence of non-additive gene action and environmental factors. Principal component analysis identified seven principal components accounting for 85.178 % of the total variation. The first 2 components explained 40.59 % of the variability, with plant height, number of branches, flower diameter and length of anther appendages contributing significantly to PC1, while leaf width, length of corolla tube and flower weight were major contributors to PC2. This study provides valuable insight into the genetic architecture of Adenium traits, offering a foundation for future breeding efforts aimed at developing improved varieties for commercial and ornamental purposes. These findings highlight the potential for genetic improvement in Adenium through selective breeding, particularly for traits with high heritability and genetic advance.